Research on estimating effective order of radio channel in OFDM systems - LI Guo-song; ZHOU Zheng-ou (Tongxin xuebao)
In wireless communication system based on OFDM,the character of LS algorithm’s result in time-domain was paid much attention to.At the same time,the character of Channel Impulse Response（CIR）in time-domain was taken into account.It was proposed to detect energy of CIR’s tap of LS algorithm’s result in time-domain and search the effective order of radio channel conversely.By theoretical analyses and computer simulation,it is indicated that this method shows good performance in estimating effective order of radio channel.